The Epigenesis of Rationality: Kant with Neurobiology (KULT_online, 2016)
One might wonder how two seemingly opposed concepts ended up in the same book title: epigenesis and rationality. One pertaining to biology, the other to philosophy, cognitive and neurosciences; one describing a modality of change of the living, the other usually taken to be unchangeable, universal; one empiric, the other traditionally linked to the non-sensible; one describing the structuring influence of the environment on organisms, the other the supposed purity of thought. At stake in French philosopher Catherine Malabou’s newest book (and her oeuvre more generally) is precisely this: trying to think the mutual in-formation of the real and the ideal, the empirical and the a priori, the material and the symbolic.